Summary of the Speech Delivered by Premier János Kádár at the Opening Session of the Newly Elected National Assembly of the Hungarian People's Republic - Héderváry, Claire de (1962)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Permanent Mission of Hungary The speech addresses the conditions of the announced general amnesty: it covers individuals accused of being war criminals, violators of legality who abused their authority during the cult of personality; crimes in connection with the counter-revolution; anti-state crimes, those convicted of small crimes and people who left the territory of the country illegally. The amnesty does not cover people who were convicted for espionage and treason.